The use of triple jump training drills in replicating movement coordination patterns - Wilson, C.; Simpson, S.; Hamill, J. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
The purpose of this study was to investigate how effective triple jump training drills are at replicating the lower extremity coordination patterns utilised during the triple jump. Relative motion plots and a modified version of the vector coding technique were used to quantify the coordination patterns of the lower extremities in the triple jump and four related training drills. Differences were found to exist in the coordination patterns between the triple jump and static, but not dynamic, drills and these differences were mainly in the swing (free) leg. The results of this study suggest that if the primary purpose of the training drills is to replicate the movement patterns utilised in the triple jump then dynamic drills are more effective than static drills. In addition, coaches should focus on the use of the free leg during these training drills.